Pengaruh Kompetensi, Perilaku Perawat dan Supervisi terhadap Penerapan Keselamatan Pasien (Patient safety) - imelda, imelda; Suprapto, Sentot Imam; Puspitasari, Yenny (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Implementation of Patient Safety Goals at Tora Belo Hospital, especially inpatients, it is still found that the implementation of nursing actions is not in accordance with standard operating procedures (SOP) and does not carry out patient safety procedures properly, such as the patient's identity bracelet is not attached, there is no communication between the nurse and the patient/patient's family in the procedure for providing nursing services, as well as the absence of safety guards where the patient is at risk of falling. To determine the effect of competency, nurse behavior and supervision on the implementation of patient safety at Tora Belo Sigi Hospital. Quantitative research using a cross sectional approach. Samples were collected by means of simple random sampling, as many as 105 nurses. the results of Multiple Linear Regression analysis show that the value of Sig. for the effect of the competency variable (X1) on the patient safety variable (Y) is 0.025 t table 1.9837, so it can be concluded that there is a positive and significant influence between competence and the implementation of patient safety in the Hospital. Tora Belo, Sigi Regency. In testing the behavior variable, the value of Sig. for the effect of the behavioral variable (X2) on the patient safety variable (Y) is 0.045 t table 1.9837, so it can be concluded that there is a positive and significant influence between behavior and the implementation of patient safety in hospitals. Tora Belo, Sigi Regency, and the value of Sig. for the effect of the supervision variable (X3) on the patient safety variable (Y) is 0.005 t table 1.9837, which can be concluded that there is a positive and significant effect between supervision and the application of patient safety in hospitals. Tora Belo, Sigi Regency.Keywords: Competence, Behavior, Supervision, Patient Safety, Nurse